The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijms19124003
|View full text |Cite
|
Sign up to set email alerts
|

α-Chymotrypsin Immobilized on a Low-Density Polyethylene Surface Successfully Weakens Escherichia coli Biofilm Formation

Abstract: The protease α-chymotrypsin (α-CT) was covalently immobilized on a low-density polyethylene (LDPE) surface, providing a new non-leaching material (LDPE-α-CT) able to preserve surfaces from biofilm growth over a long working timescale. The immobilized enzyme showed a transesterification activity of 1.24 nmol/h, confirming that the immobilization protocol did not negatively affect α-CT activity. Plate count viability assays, as well as confocal laser scanner microscopy (CLSM) analysis, showed that LDPE-α-CT sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 91 publications
(115 reference statements)
1
22
0
Order By: Relevance
“…There are several anti-fouling catheters including those coated with hydrogels (most popular) [27,28], poly(tetrafluoroethylene) [34][35][36][37][38], polyzwitterions [39][40][41], and poly(ethylene glycol) [42][43][44][45][46]. Furthermore, surface topography modification [47][48][49][50] and enzymes-immobilized coatings [51][52][53][54][55][56][57][58] have been explored for prevention of microbial colonization and biofilm formation. These polymers and modifications are discussed in detail in this section.…”
Section: Approaches To Restriction Of Cauti By Inhibition Of Microbiamentioning
confidence: 99%
See 2 more Smart Citations
“…There are several anti-fouling catheters including those coated with hydrogels (most popular) [27,28], poly(tetrafluoroethylene) [34][35][36][37][38], polyzwitterions [39][40][41], and poly(ethylene glycol) [42][43][44][45][46]. Furthermore, surface topography modification [47][48][49][50] and enzymes-immobilized coatings [51][52][53][54][55][56][57][58] have been explored for prevention of microbial colonization and biofilm formation. These polymers and modifications are discussed in detail in this section.…”
Section: Approaches To Restriction Of Cauti By Inhibition Of Microbiamentioning
confidence: 99%
“…α-CT is a serine endopeptidase that cleaves peptide bonds by attacking the unreactive carbonyl group [52]. Based on the properties of α-CT, Catto and collaborators assessed whether α-CT will disrupt biofilm formation [55] since biofilm matrix consists of proteins, extracellular DNA, and polysaccharides [67]. In this in vitro study, α-CT was covalently immobilized on a low-density polyethylene (LDPE) pieces and incubated with LB media containing E. coli MG1655 in a CDC biofilm reactor with continuous stirring.…”
Section: α-Chymotrypsin (α-Ct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, selection pressure decreases, limiting resistant-drug development, and potentially reinstating the efficacy of traditional antimicrobials [69]. Several natural and synthetic compounds, as well as matrix-targeting enzymes based on the previous biocide-free anti-biofilm mechanisms of action, have been coated or immobilized on polymeric surfaces, providing promising, eco-friendly, bio-inspired, anti-biofilm materials able to replace, or integrate with, presently dominating biocide-based approaches [69,70,71,72,73,74].…”
Section: Anti-biofilm Polymeric Surfacesmentioning
confidence: 99%
“…Sajeevan et al [77] impregnated silicon catheter tubes with anacardic acids that efficiently inhibited Staphylococcus aureus colonization and biofilm formation on its surface both in vitro and in vivo. Spadoni-Andreani et al [73] demonstrated that polypropylene surfaces coated with proteases weakened adhesion and increased the dispersion of Candida albicans biofilm cells and Cattò et al [74] proved that the proteases α-chymotrypsin prevented E. coli biofilm formation on polyethylene materials…”
Section: Anti-biofilm Polymeric Surfacesmentioning
confidence: 99%